Understanding the Process Involved in Post-COVID Headache Development and What the Literature Suggests as Therapeutic Approach: A Literature Review - Lima, Raynrich Kevin Assis; Santos, Isabela Cacau Sousa; Santos, Gabriela Cacau Sousa; Lima, Rayndrick Kelryn Assis; Nogueira, André Marinho Paiva (Headache Medicine, 2023)
Full abstract in PDF.